(untitled) (Italian Journal of Public Health, 2004)
Despite the great variety of regional and national health reports that have been drawn up in the European Region, authors and users demand that health reports should be conceived as an instrument for health policy. Under the research project “Evaluation of national and regional health reports (Eva PHR)” within the Health Monitoring Programme of the European Union, the policy impact of health reports drawn up in 19 European countries has been analysed with the objective of identifying best practice models. Modelled on an agreed list of criteria, regional and national health reports were analysed with regard to their contents, structure and political relevance. Simultaneously, a qualitative analysis of semi-structured interviews held with policy makers (politicians, decision-makers in administration and stakeholders) on the experiences, ideas and expectations they have with regard to health reporting was carried out. The presently prevailing practice of descriptive health reporting is characterised by a great heterogeneity among all received reports and by a discrepancy between the expectations of policy makers and actual health reporting. Whereas most health reports in Europe focus on covering the widest possible range of issues and on presenting existing data and indicators accordingly, most decision makers attach considera- ble importance to linking epidemiology with information about health care provision, financing and evalua- tion of programmes and activities. To increase the policy relevance of public health reporting, authors should work in close collaboration with policy makers and consider different kinds of products with differing forms and content. Furthermore, the development of methodical instruments for routine policy oriented health reporting could close the current gap between the perceptions of authors and users.